Optimization of biodiesel synthesis process from nyamplung (calophyllum inophyllum) oil using thermal air sparging method - Nasrul Ilminnafik; Dani Hari Tunggal Prasetiyo; Welayaturromadhona; Audiananti Meganandi Kartini; Bekti Palupi; Suyitno (Universitas Muhammadiyah Magelang, 2026)
This study investigated the optimization of biodiesel production from nyamplung (Calophyllum inophyllum) oil using a Thermal Air Sparging (TAS) reactor with NaOH catalyst. Crude oil containing 18.2% free fatty acids (FFA) underwent a two-stage acid esterification to reduce the acidity below the 2% threshold required for efficient alkaline transesterification. To assess the combined effects of thermal and hydrodynamic variables, a 3² full factorial experimental design with three replications was used, encompassing a reaction temperature of 30–40 °C and a hot air flow rate of 1.0–2.0 L min⁻¹. The produced biodiesel was characterized for density, kinematic viscosity, flash point, and heating value according to ASTM D4052, D445, D93, and D240, respectively. These values ​​were then evaluated against SNI 7182:2015 specifications. Optimal operating conditions were achieved at 35°C and a flow rate of 1.5 L min⁻¹. Reaction temperature emerged as the primary factor influencing biodiesel conversion, while hot air flow rate predominantly affected interfacial contact and residence time. Under these conditions, the biodiesel exhibited a density of 0.867 g·cm⁻³, a kinematic viscosity of 4.67 cSt, a flash point of 183.2°C, a calorific value of 10,283.20 cal·g⁻¹, and a conversion yield of 85.43%. This performance is attributed to the combined effects of heat transfer and dispersion driven by microbubbles, which continuously renew the interfacial surface area between the reactants and promote a more homogeneous reaction environment at atmospheric pressure and relatively low temperature. In contrast to mechanical stirring systems and other high-energy intensification methods, the TAS configuration allows for intensification of the thermofluidic process, reducing reaction time, stabilizing fuel properties, and lowering overall energy consumption. These results demonstrate the potential of TAS as a practical and scalable method for converting non-edible oils with high free fatty acid content into biodiesel through a low-energy process.